Predictive Value of Osteoporosis Risk Factors for Bone Loss - Şafak S. Karamehmetoğlu; İlhan Karacan; İmdat Özkul; Merih Eryavuz Sarıdoğan (Türk Osteoporoz Dergisi, 2003)
Osteoporosis is a serious and costly public health problem. It is important that subjects with risk for bone loss determine in a way that is economical and practical. The aim of the current study was to investigate the predictive value of osteoporosis risk factors for bone loss. The study included 445 female subjects. The mean age was 53.1 ± 12.0 years, mean body weight was 73.1 ± 11.7 kg, mean body height was 1.60 ± 0.05 m, and mean body mass index was 28.2 ± 4.4 kg/m2. Each subjects filled out a questionnaire. Bone mineral density was evaluated in the calcaneus using quantitative ultrasound. Subjects with no risk factors were 144 (32.4 %), with one risk factor was 152 (34.2 %), with two risk factors were 104 (23.4 %) and with three risk factors were 45 (10.1 %). Bone loss was found in 68 patients. The number of subjects with at least one risk factor and bone loss was 55 (12.3 %). The number of subjects with no risk factor and bone loss was 131 (29.4 %). Kappa ratio was 0.065 (p=0.011). In conclusion, this study suggests that comprehensive osteoporosis risk factors questionnaire should be used to determine subjects with risk for bone loss.